Early nitrogen supply as an alternative management for a cover crop-maize sequence under a no-till system - Momesso, Letusa [UNESP]; Crusciol, Carlos A. C. [UNESP]; Soratto, Rogério P. [UNESP]; Nascimento, Carlos A. C.; Rosolem, Ciro A. [UNESP]; Moretti, Luiz G. [UNESP]; Kuramae, Eiko E.; Cantarella, Heitor (Springer Nature, 2021)
Optimizing agronomic efficiency (AE) of nitrogen (N) fertilizer use by crops and enhancing crop yields are challenges for tropical no-tillage systems since maintaining crop residues on the soil surface alters the nutrient supply to the system. Cover crops receiving N fertilizer can provide superior biomass, N cycling to the soil and plant residue mineralization. The aims of this study were to (i) investigate N application on forage cover crops or cover crop residues as a substitute for N sidedressing (conventional method) for maize and (ii) investigate the supply of mineral N in the soil and the rates of biomass decomposition and N release. The treatments comprised two species, i.e., palisade grass [Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster] and ruzigrass [Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins], and four N applications: (i) control (no N application), (ii) on live cover crops 35 days before maize seeding (35 DBS), (iii) on cover crop residues 1 DBS, and (iv) conventional method (N sidedressing of maize). The maximum rates of biomass decomposition and N release were in palisade grass. The biomass of palisade grass and ruzigrass were 81 and 47% higher in N application at 35 DBS compared with control in ruzigrass (7 Mg ha−1), and N release followed the pattern observed of biomass in palisade and ruzigrass receiving N 35 DBS (249 and 189 kg N ha−1). Mineral N in the soil increased with N application regardless of cover crop species. Maize grain yields and AE were not affected when N was applied on palisade grass 35 DBS or 1 DBS (average 13 Mg ha−1 and 54 kg N kg−1 maize grain yield) compared to conventional method. However, N applied on ruzigrass 35 DBS decreased maize grain yields. Overall, N fertilizer can be applied on palisade grass 35 DBS or its residues 1 DBS as a substitute for conventional sidedressing application for maize.
Keywords: Brachiaria spp; Cover crop; Food production; Nitrogen supply; Tropical agriculture; Zea mays